2009
DOI: 10.2134/agronj2008.0014x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of High Yielding, Early‐Planted Soybean in Indiana

Abstract: A trend toward early planting of soybean [Glycine max (L.) Merr.] in Indiana results in higher yield, but the limit to which a positive response to early planting occurs has not been evaluated. Our objective was to determine how early planting aff ects yield components and seed composition of indeterminate soybean planted in late March through early June in Indiana. Th ree cultivars (Pioneer brand 92M61, Becks brand 321NRR, and Becks brand 367NRR) were sown at six planting dates (late March through early June)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
102
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(126 citation statements)
references
References 25 publications
13
102
4
Order By: Relevance
“…Pedersen and Lauer (2004) did not verify interaction between sowing date and cultivars for number of pods per area and seeds per pod, as well as in our study. Robinson et al (2009), in a study with sowing dates and cultivars, found important correlation between yield and number of pods according to date of sowing, where late sowing decreased the number of pods for all cultivars, reflecting negatively in seed yield. In the conditions of this study, late sowing did not reduced the number of pods per area.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Pedersen and Lauer (2004) did not verify interaction between sowing date and cultivars for number of pods per area and seeds per pod, as well as in our study. Robinson et al (2009), in a study with sowing dates and cultivars, found important correlation between yield and number of pods according to date of sowing, where late sowing decreased the number of pods for all cultivars, reflecting negatively in seed yield. In the conditions of this study, late sowing did not reduced the number of pods per area.…”
Section: Discussionmentioning
confidence: 94%
“…The sowing date is possibly the main and less expensive crop management, which impacts the soybean grain yield (Popp et al, 2002;Robinson et al, 2009). In soybean crop, early sowing can increase grain yield (Wilcox & Frankenberger, 1987) or not change it (Grau et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a strategy to boost Japanese soybean yield is needed based on both agronomic practices and genetics. Optimization of sowing dates is the most important and least expensive agronomic practice that affects soybean yield Robinson et al, 2009 . Some researchers have suggested that earlier sowing dates contributed to recent soybean yield gains in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers have suggested that earlier sowing dates contributed to recent soybean yield gains in the United States. For example, sowing soybeans in late April and early May is currently recommended in the Midwestern United States to achieve the maximum seed yield Bastidas et al, 2008;De Bruin and Pedersen, 2008;Robinson et al, 2009 . Sowing before the optimal date is restricted mainly by cool soil temperatures Hu and Wiatrak, 2012 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation